Estimating the number of unit roots: A multiple decision approach - Robert M. Kunst (Institute for Advanced Studies (IHS), 1995)
The problem of detecting unit roots in univariate and multivariate time series data is treated as a problem of multiple decisions instead of a testing problem, as is otherwise common in the econometric and statistical literature. Four examples for such multiple decision designs are considered: first- and second-order integrated univariate processes; conintegration in a bivariate model; seasonal integration for semester data; seasonal integration for quarterly data. In all cases, restrictedly optimum decision rules are found for finite samples based on Monte Carlo simulation. – – Das Problem, Einheitswurzeln in univariaten und multivariaten Zeitreihen aufzufinden, wird als Problem multipler Entscheidungen behandelt anstatt als Testproblem, wie es sonst in der ökonometrischen und statistischen Literatur üblich ist. Vier Beispiele solcher multipler Entscheidungsproblem werden berücksichtigt: univariate Prozesse mit Integration erster und zweiter Ordnung; Kointegration in einem bivariaten Modell; saisonale Integration für Semesterdaten; saisonale Integration für Quartalsdaten. In allen Fällen werden beschränkt optimale Entscheidungsregeln für endliche Stichproben durch Monte-Carlo-Simulationen ermittelt.
Keywords: C22; C32; C49; 330; multiple decision; unit roots; autoregressive processes